EPIDEMIOLOGY OF CUTANEOUS LEISHMANIASIS IN DISTRICT KARAK, KHYBER PAKHTUNKHWA, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Cutaneous Leishmaniasis is a vector-borne infection caused by flagellated parasitic protozoans in the genus Leishmania. .  The bite of an infected female sandfly from the genera Phlebotomus or Lutzomyia can spread the infectious promastigote stage to humans.  In many regions of Pakistan, especially Khyber Pakhtunkhwa, CL is regarded as one of the main public health issues. The goal of the current study was to look at the clinical and demographic trends of CL in Pakistan's Karak District, Khyber Pakhtunkhwa.  Between March 2022 and April 2023, the survey was conducted with both local residents and temporarily displaced people (TDPs) living in 14 distinct villages within the district. There is total no588 people that were analyzed, 35 were TDPs and 553 were members of the local population. In the local population, the general prevalence of CL was 7.80%, whereas in TDPs, it was 7.00%.  According to the age-wise distribution, children ages 1 to 10 had the highest occurrence in both categories, suggesting that younger people are more susceptible.  Males had a much higher incidence than females, according to a gender-wise analysis. This could be because males are more likely to be exposed to sandfly bites outside.  A comparison of the villages showed that Panos had the highest prevalence (11.00%) while Alamsheri had the lowest frequency (1.40%). The findings suggest that CL remains endemic in the Karak District, with notable variation in prevalence across different age groups, genders, and localities. These results highlight the need for targeted awareness programs, preventive measures, and vector control strategies to reduce disease transmission. Moreover, timely diagnosis and effective treatment facilities are required, particularly for vulnerable groups such as children and displaced population.These results indicate that cutaneous Leishmaniasis as much common in male individual as compared to female. Suggesting that male individual are more exposed to the fly.